2021
DOI: 10.1186/s40359-021-00558-x
|View full text |Cite
|
Sign up to set email alerts
|

Vision loss, vision difficulty and psychological distress in South Africa: results from SANHANES-1

Abstract: Background Psychological distress in vision impairments and blindness is a complex issue and a major public health concern. Sudden adjustments in routine lifestyle and career aspirations in such persons culminate in and/or aggravate their level of stress. Yet, psychological distress in persons with visual difficulties and vision loss in South Africa is poorly understood. We investigated the association between psychological distress and self-reported vision difficulties as well as clinician-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…Consistent with these studies, the distribution of different categories of VI was found to increase with age, particularly among the older population in our study, with the proportion of participants who were blind among the adult age group being almost double the proportion who were blind in all other age groups combined. Similar findings were recorded in other studies [ 9 , 19 , 21 , 22 , 23 , 24 , 25 ]. Although these studies were conducted in different settings compared to ours, the age range for adults in these studies and ours overlap; hence, a comparison of our study to these studies in terms of tested age groups is a valid one.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with these studies, the distribution of different categories of VI was found to increase with age, particularly among the older population in our study, with the proportion of participants who were blind among the adult age group being almost double the proportion who were blind in all other age groups combined. Similar findings were recorded in other studies [ 9 , 19 , 21 , 22 , 23 , 24 , 25 ]. Although these studies were conducted in different settings compared to ours, the age range for adults in these studies and ours overlap; hence, a comparison of our study to these studies in terms of tested age groups is a valid one.…”
Section: Discussionsupporting
confidence: 92%
“…Individuals with eye diseases in Sub-Saharan Africa may experience heightened stress and mental health challenges due to the impact of their condition on daily activities, social interactions, and overall well-being (Courtright et al, 2016). The psychological burden of coping with vision loss can lead to feelings of frustration, anxiety, and depression, affecting their mental health (Akuffo et al, 2021;Courtright et al, 2016), hence the need for psychological assessment in eye clinics in SSA.…”
Section: Factors Impacting Vision Care In Sub-saharan Africamentioning
confidence: 99%
“… 10 , 11 VI may also increase other physical challenges, such as cognitive decline, 12 , 13 reduced vision-related quality of life (VRQoL), 14 and increased risk of chronic disease and death. 15 , 16 The elderly with VI will also have psychological problems, 17 such as anxiety and depression. 18 , 19 The incidence of depression and anxiety of the elderly with VI is twice that of the general elderly.…”
Section: Introductionmentioning
confidence: 99%
“…with VI will also have psychological problems, 17 such as anxiety and depression. 18,19 The incidence of depression and anxiety of the elderly with VI is twice that of the general elderly.…”
mentioning
confidence: 99%